2010
DOI: 10.4236/ns.2010.26067
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny of γ-proteobacteria inferred from comparisons of 3’ end 16S rRNA gene and 5’ end 16S-23S ITS nucleotide sequences

Abstract: The phylogeny of γ-proteobacteria was inferred from nucleotide sequence comparisons of a short 232 nucleotide sequence marker. A total of 64 γ-proteobacterial strains from 13 Orders, 22 families, 40 genera and 59 species were analyzed. The short 232 nucleotide sequence marker used here was a combination of a 157 nucleotide sequence at the 3' end of the 16S rRNA gene and a 75 nucleotide sequence at the 5' end of the 16S-23S Internal Transcribed Spacer (ITS) sequence. Comparative analyses of the 3' end of the 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 35 publications
(39 reference statements)
0
5
0
Order By: Relevance
“…Owing to its higher rate of nucleotide substitutions, the 67-75 bp from the 5' end of the 16S-23S ITS added resolving power among closely related species from same genus. This marker had proven useful in reconstructing the phylogenies of the genus Bacillus and closely-related genera [32], the Order Bacillales [33] and the Class γ-proteobacteria [26] in accordance with accepted phylogenies inferred from much more comprehensive datasets. This marker presented several advantages over the use of the entire 16S rRNA gene or the 16S-23S ITS or the generation of extensive phenotypic and genotypic data in phylogenetic analyses.…”
Section: Resultsmentioning
confidence: 69%
See 2 more Smart Citations
“…Owing to its higher rate of nucleotide substitutions, the 67-75 bp from the 5' end of the 16S-23S ITS added resolving power among closely related species from same genus. This marker had proven useful in reconstructing the phylogenies of the genus Bacillus and closely-related genera [32], the Order Bacillales [33] and the Class γ-proteobacteria [26] in accordance with accepted phylogenies inferred from much more comprehensive datasets. This marker presented several advantages over the use of the entire 16S rRNA gene or the 16S-23S ITS or the generation of extensive phenotypic and genotypic data in phylogenetic analyses.…”
Section: Resultsmentioning
confidence: 69%
“…In previous studies, we showed that a DNA sequence from 3' end 16S rRNA gene and 5' end 16S-23S ITS could be used as a marker in the reconstruction of phylogenies in the Gram-positive genus Bacillus and closely-related genera [32], the Gram-positive Order Bacillales [33], and the Gram-negative Class γ-proteobacteria [26]. This maker ranged in size from 220 bp to 232 bp.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, we assessed the usefulness of the 220 bp marker by extending its analyses at a higher taxonomic level, the Gram-positive Order Bacillales [29]. In parallel, a similar marker was used to infer the phylogeny of the Gram-negative Class γ-proteobacteria [33]. In the current study, we further analyze the resolving power of this marker in inferring the phylogeny at a much lower taxa level: the Bacillus cereus group.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, in parallel, a similar maker was tested and shown to be able to reconstruct the phylogeny of the Class γ-proteobacteria [19].…”
Section: Discussionmentioning
confidence: 99%